Wage setting and wage moderation in Belgium: A never-ending and already-old story in the wake of the 'new European economic governance'. Issue 2 (June 2022) - Dorssemont, Filip
Wage setting can be defined as the procedures which determine the remuneration which needs to be paid to employees as the counterpart of their work. The ancillary relationship between wage moderation and the new economic governance has never been expressed as clearly as in the Europlus Pact. The new economic governance (NEG) of the European Union has fostered wage moderation. This approach to wage setting and wage moderation is analysed from the perspective of the freedom of collective bargaining as a fundamental right, and on the basis of a national case study (Belgium). In order to carry out this analysis, the national wage moderation policies adopted in Belgium prior to the era of the NEG need to be examined first. The recommendations addressed to Belgium to reform the wage-setting system will then be analysed, as well as the impact they had both in confirming the existing system of wage moderation and the attempts to strengthen the restrictions imposed on collective autonomy. In light of these findings, these restrictions of collective autonomy are assessed on the basis of the freedom of collective bargaining, understood as a fundamental right.